Sex Work on Campus - Stewart, Terah J. (Interdisciplinary Research in Gender, 2022)
Sex Work On Campus examines the experiences of college students engaged in sex work and sparks dialogue about the ways educators might develop a deeper appreciation for-and praxis of-equity and justice on campus. Analysing a study conducted with seven college student sex workers, the book focuses on sex work histories, student motivations and how power (or lack thereof) associated with social identity shapes experiences of student sex work. It examines what these students learn because of sex work, and what college and university leaders can do to support them. These findings are combined in tandem with analysis of current research, popular culture, sex work rights movements, and exploration of legal contexts. This fresh and important writing is suitable for students and scholars in sexuality studies, gender studies, sociology, and education.